Perfluoroalkyl and polyfluoroalkyl substances and human fetal growth: A systematic review. (January 2015) - Bach, Cathrine Carlsen; Bech, Bodil Hammer; Brix, Nis; Nohr, Ellen Aagaard; Bonde, Jens Peter Ellekilde; Henriksen, Tine Brink
Abstract Background: Exposure to perfluoroalkyl and polyfluoroalkyl substances (PFASs) is ubiquitous in most regions of the world. The most commonly studied PFASs are perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA). Animal studies indicate that maternal PFAS exposure is associated with reduced fetal growth. However, the results of human studies are inconsistent. Objectives: To summarize the evidence of an association between exposure to PFASs, particularly PFOS and PFOA, and human fetal growth. Methods: Systematic literature searches were performed in MEDLINE and EMBASE. We included original studies on pregnant women with measurements of PFOA or PFOS in maternal blood during pregnancy or the umbilical cord and associations with birth weight or related outcomes according to the PFAS level. Citations and references from the included articles were investigated to locate more relevant articles. Study characteristics and results were extracted to structured tables. The completeness of reporting as well as the risk of bias and confounding were assessed. Results: Fourteen studies were eligible. In utero PFOA exposure was associated with decreased measures of continuous birth weight in all studies, even though the magnitude of the association differed and many results were statistically insignificant. PFOS exposure and birth weight were associated in some studies, while others found no association. Conclusions: Higher PFOS and PFOA concentrations were associated with decreased average birth weight in most studies, but only some results were statistically significant. The impact on public health is unclear, but the global exposure to PFASs warrants further investigation.